2007
DOI: 10.1093/jat/31.8.469
|View full text |Cite
|
Sign up to set email alerts
|

Vitreous Fluid Quantification of Opiates, Cocaine, and Benzoylecgonine: Comparison of Calibration Curves in Both Blood and Vitreous Matrices with Corresponding Concentrations in Blood

Abstract: Vitreous fluid specimens are often used in the Montgomery County Coroner's Office as a second matrix confirmation for both cocaine and opiate analyses. In this manuscript, calibration curves constructed for both vitreous and blood were used to quantify vitreous specimens to evaluate if any matrix effects occur when measuring vitreous specimens using a calibration curve in blood. Cases that screened positive by ELISA for cocaine metabolite and opiates were confirmed by solid-phase extraction. Gas chromatography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 8 publications
1
9
0
5
Order By: Relevance
“…With particularly high concentrations of esterases found in liver, heart, lung, kidney, and blood. 25 Our study shows that as with other studies 24,26,27 vitreous is the best sample for the detection of 6-MAM being detected in 100% of cases. In blood, the 6-MAM was most stable in fluoride/oxalate preserved samples where it was detected in 61% of samples.…”
Section: Qualitative Screeningsupporting
confidence: 87%
“…With particularly high concentrations of esterases found in liver, heart, lung, kidney, and blood. 25 Our study shows that as with other studies 24,26,27 vitreous is the best sample for the detection of 6-MAM being detected in 100% of cases. In blood, the 6-MAM was most stable in fluoride/oxalate preserved samples where it was detected in 61% of samples.…”
Section: Qualitative Screeningsupporting
confidence: 87%
“…En ce qui concerne la morphine, sa diffusion dans l'HV est relativement limitée. Sur 15 cas de décès impliquant la prise d'opiacés, Antonides et al retrouvent que la concentration en morphine dans le sang est plus élevée que dans l'HV dans 71 % des cas [4]. Wyman et al ont pu calculer un ratio de l'ordre de 0,36 pour le rapport des concentrations en morphine entre l'HV et le sang sur 25 autopsies.…”
Section: Opiacés Dans L'humeur Vitréeunclassified
“…C'est ce qu'ont observé Antonides et al dans 72 % de leurs cas (N = 40). L'inverse est observé pour la benzoylecgonine, dont la concentration est supérieure dans le sang dans 78 % des cas [4]. Le cocaéthylène peut aussi être détecté dans l'HV mais sa corrélation avec les concentrations sanguines est plus aléatoire (r = 0,433) [15].…”
Section: Cocaïne Dans L'humeur Vitréeunclassified
See 1 more Smart Citation
“…Some laboratories have not tested the matrix effect and have only used blood calibration curves to quantify vitreous humor samples. In fact, Antonides et al [33] have not observed any significant variability in vitreous humor concentration quantified using calibrators prepared in blood matrix, and the comparison between the measurement of vitreous values using a calibration curve in the blood matrix and in the vitreous matrix resulted in a difference of no more than 20% of their averages. In the present study, however, the analysis of the variances and the means obtained between the blood and saline solution sets of samples showed a significant difference in analyte responses at all concentration levels (30,550 and 1100 ng/mL).…”
Section: Methods Validationmentioning
confidence: 98%